Comportamento sedentário e nível de atividade física na síndrome da fragilidade - Carnavale, Bianca Ferdin (Universidade Federal de São Carlos, 2022)
Physical inactivity and sedentary behavior influence the frailty syndrome progression. To assess the physical activity level and sedentary behavior, the accelerometer has been used as an objective measure. Due to reversible character of the frailty syndrome, interventions based on physical exercises have been proposed for frail older adults and those at risk of frailty. In front of the exposed, this thesis was divided into two studies, and Study I was entitled “Analysis of physical activity level and sedentary behavior by accelerometry in frailty syndrome: a cross-sectional study”. This study aimed to identify the physical activity level and prolonged sedentary bouts in frail, pre-frail and non-frail older adults, using an accelerometer with a postural classification device. After this study, an intervention protocol was developed, based on multicomponent exercises, for pre-frail older adults. Study II, entitled “Effects of a multicomponent training and detraining on frailty status, physical activity level, sedentary behavior and physical performance of pre-frail older adults: blinded randomized controlled trial”, aimed to evaluate the effects of a training multicomponent protocol and detraining on frailty status, physical activity level, sedentary behavior and physical performance in pre-frail older adults. The multicomponent training protocol was performed in 16 weeks and had a 6-week follow-up. The protocol consisted of warm-up, aerobic, balance, resistance and flexibility exercises. The results of Study I presented that using an accelerometer with posture classification, it was not possible to differentiate sedentary behavior of frail older adults from pre-frail and non-frail. Furthermore, the frail group have a reduced in physical activity level, compared to the non-frail group. Study II demonstrated that multicomponent training was effective in reversing frailty status and improving gait speed in pre-frail older adults. However, there was no change in the physical activity level and sedentary behavior, requiring other strategies for behavioral change.
Sedentary behavior and physical activity level in frailty syndrome
Keywords: Fragilidade; Idoso; Exercício físico; Comportamento sedentário; Treinamento multicomponente; Acelerometria; Frailty; Older adults; Physical exercise; Sedentary behavior; Multicomponent training; Accelerometry; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL